Kode Etik Jaksa Dan Dilema Etus Dalam Implementasi Restorative Justice - Dyana Subairi; Nina Agus Hariati (Marwah Hukum, 2026)
This study examines the function of the prosecutor's code of ethicsas a moral and professional guideline in the implementation of restorative justice inIndonesia. Using a normative legal approach, this studyanalyzes various regulations and literature to evaluate ethical issuesarising from the policy of discontinuing prosecution. The findings show thatalthough the code of ethics emphasizes the importance of integrity and professionalism,the implementation of restorative justice is often hampered by external pressures,imbalances between victims and perpetrators, and the influence of institutions.The success of restorative justice is highly dependent on strengthening ethical oversight, improving prosecutors' mediation skills, and developing consistent standard operating procedures. The balance between prosecutor integrity,structural oversight, and procedural clarity is key to ensuringthat the case resolution process is fair andaccountable.